HUMAN RIGHTS IN THE NOVEL THE HATE U GIVE BY ANGIE THOMAS - Nur Ajeng Syahputri; Ratna Sari Dewi (Fakultas Sastra UMN AL Washliyah, 2023)
This research analyzes the extrinsic elements and human rights principles in the novel. The Hate U Give is a novel about a teenager who suffered from discrimination as part of African American community. This research shown the treatment of human rights principles violations and strong relationship between the writer and her literature work. The purpose of this research is first, to identify extrinsic element in the novel. Second, to analyze human rights practice done by society in this novel. This study uses extrinsic approach by Warren and Wellek (1956). The method used is descriptive qualitative method to analyze the data in this research. The data sources are taken from the quotes in the novel. The finding in the research are first, this novel is a motivation of the writer to spread awareness about her childhood memory. Second, human rights principles are violated such as universality and inalienability, participation and inclusion, indivisibility, accountability and rule of law, lastly equality and non-discrimination.